The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1130/g32846.1
|View full text |Cite
|
Sign up to set email alerts
|

Going nano: A new step toward understanding the processes governing freshwater ooid formation

Abstract: Marine and freshwater ooids were historically thought to form by purely physicochemical processes in turbulent environments. Recently, organomineralization has been identifi ed as a key process for the initiation of freshwater ooid cortex formation, but the exact biochemical mechanism(s) involved and subsequent contribution to the development of the growing cortex remain unknown. Here, we show that photosynthetic microbes not only enhance early carbonate precipitation around the ooid nucleus but also control t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 25 publications
3
77
1
3
Order By: Relevance
“…Amorphous Mg-Si precipitates have previously been reported in carbonate environments, and are always associated with microbial activity [13][14][15] . It has also been demonstrated that am Mg-Si enhances fossilization, and is commonly found in the rock record 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amorphous Mg-Si precipitates have previously been reported in carbonate environments, and are always associated with microbial activity [13][14][15] . It has also been demonstrated that am Mg-Si enhances fossilization, and is commonly found in the rock record 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our data indicate a primary origin for these am Mg-Si phases. Previous studies have established the role of cell walls and EPS as nucleation sites for am Mg-Si precipitates, leading to prokaryote fossilization 13,15 . Like EPS, the viral capsid is composed of proteins containing reactive carboxyl and amine groups 16,17 that are known to have a key role in cation binding 6 and thus, can act as a template for mineralization 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Êàê èçâåñòíî [20], â ñîâðå-ìåííûõ ãëèíèñòûõ ïîðîäàõ è èëàõ îáðàçîâàíèå ôðàìáîè-äàëüíîãî ïèðèòà îáóñëîâëåíî ñóùåñòâîâàíèåì ýâêñèííîé îáñòàíîâêè â ïðèäîííûõ âîäàõ è òðàêòóåòñÿ êàê ðåçóëüòàò ïèðèòèçàöèè íåïîñðåäñòâåííî íàíîáàêòåðèé. Èçó÷åíèå ñîâðåìåííûõ îêñèãèäðîêñèäîâ aeåëåçà è ôðàìáîèäàëüíî-ãî ïèðèòà íà ó÷àñòêàõ ìåòàíîâûõ âûñà÷èâàíèé [27] ïîêà-çàëî, ÷òî èìåííî àêòèâíîñòü ñóëüôàòðåäóöèðóþùèõ áàê-òåðèé â îáñòàíîâêàõ ñ íèçêîé êîíöåíòðàöèåé êèñëîðîäà îáåñïå÷èâàåò óñëîâèÿ äëÿ îáðàçîâàíèÿ ñóëüôèäîâ aeåëåçà.…”
Section: îáñóAeäåíèå ðåçóëüòàòîâunclassified
“…Òàêîé ìèêðîýëåìåíòíûé ñîñòàâ â ìèíåðàëè-çîâàííûõ áèîïëåíêàõ ãîâîðèò î ñèëèêàòíîì ñîñòàâå ãëè-êîêàëèêñà, ÷òî ÿâëÿåòñÿ äîâîëüíî òèïè÷íûì, îñîáåííî â ìåçîçîéñêèõ òîëùàõ [29]. Äàaeå ïðè ôîðìèðîâàíèè èçâåñ-òêîâûõ îîèäîâ â ïðåñíîâîäíûõ áàññåéíàõ åùå äî êàëüöè-òèçàöèè ïðîèñõîäèò ìèíåðàëèçàöèÿ ãëèêîêàëèêñà ñ îá-ðàçîâàíèåì ðåíòãåíîàìîðôíîãî ìàãíåçèàëüíîãî ñèëèêà-òà [27]. Ïðîöåññû áèîèíäóöèðóåìîé ìèíåðàëèçàöèè ôåð-ðîëèòîâ ðàçëè÷àþòñÿ â çàâèñèìîñòè îò òèïà áàêòåðèé -aeåëåçîîêèñëÿþùèõ èëè aeåëåçîðåäóöèðóþùèõ.…”
Section: îáñóAeäåíèå ðåçóëüòàòîâunclassified